2006
DOI: 10.1056/nejmc062388
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate, Increased Bone Formation, and Secondary Hyperparathyroidism

Abstract: T h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 355;23 www.nejm.org december 7, 2006 * Plus-minus values are means ±SD. Statistical analyses were performed with the use of a mixed-models approach to repeated measures (PROC Mixed software, SAS, version 9.1). Significant time effects were investigated post hoc with the use of the Tukey method to preserve an overall level of significance of 0.05. All tests were two-tailed. Reference ranges for osteocalcin, PINP, and β-CTX are for men and premenopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 3 publications
4
62
0
1
Order By: Relevance
“…(42,45,46) Decreased serum phosphate levels in imatinib-treated patients are associated with increased serum parathyroid hormone levels, decreased levels of the bone resorption marker CTX-1, and in at least some cases, a decrease in serum calcium levels. (17,40,41,(43)(44)(45) To our knowledge, there have been no published reports suggesting that changes in bone remodeling occur in patients receiving dasatinib. However, grade 3 or 4 hypophosphatemia has been reported in 11% of dasatinib-treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(42,45,46) Decreased serum phosphate levels in imatinib-treated patients are associated with increased serum parathyroid hormone levels, decreased levels of the bone resorption marker CTX-1, and in at least some cases, a decrease in serum calcium levels. (17,40,41,(43)(44)(45) To our knowledge, there have been no published reports suggesting that changes in bone remodeling occur in patients receiving dasatinib. However, grade 3 or 4 hypophosphatemia has been reported in 11% of dasatinib-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a number of studies show that decreased levels of serum phosphate occur as early as 3 months following initiation of imatinib treatment in CML and GIST patients. (17,(42)(43)(44) This decrease in serum phosphate is maintained for at least 12 months, (44) and in at least 50% of patients, the phosphate levels decrease to below the normal range (hypophosphataemia) at least once during therapy. (42,45,46) Decreased serum phosphate levels in imatinib-treated patients are associated with increased serum parathyroid hormone levels, decreased levels of the bone resorption marker CTX-1, and in at least some cases, a decrease in serum calcium levels.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similarly, a prospective study of 9 CML patients found that, relative to baseline, phosphate levels were significantly decreased after 3,6, and 18 months of imatinib treatment. 15,16 In a retrospective study of 17 CML patients receiving imatinib therapy over 17 to 69 months, there was a significant decrease in serum phosphate levels, compared with baseline. 17 In the largest study to date, Osorio et al 18 reported that 36 CML patients showed a significant decrease in serum phosphate levels after 3 months of imatinib treatment that was sustained until the final analysis at 12 months.…”
Section: Altered Calcium and Phosphate Metabolism In Imatinib-treatedmentioning
confidence: 99%
“…These studies strongly suggest that imatinib treatment results in decreased serum phosphate levels, [14][15][16][17][18] resulting in hypophosphatemia in at least 50% of patients. [12][13][14] In addition, these patients exhibit an increase in serum levels of PTH, secondary to decreased calcium levels, and increased serum 1,25 hydroxyvitamin D 3 .…”
Section: Altered Calcium and Phosphate Metabolism In Imatinib-treatedmentioning
confidence: 99%
“…To this end, current evidence suggests that patients undergoing treatment with imatinib mesylate exhibit dysregulated bone remodelling, resulting in an overall increase in trabecular bone volume. [11][12][13] This is thought to result from an inhibition of osteoclast activity and a concomitant activation of osteoblast activity by imatinib, through inhibition of c-fms and PDGFR, respectively. 5,11 Although it is unknown whether dasatinib alters the mineralization activity of osteoblasts, it could be predicted to promote osteogenesis as it is a potent inhibitor of PDGFR.…”
mentioning
confidence: 99%